2010
DOI: 10.3109/03008207.2010.516849
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 promoted MMP-2 mediated wound healing of anterior cruciate ligament fibroblasts through NF-κB

Abstract: The adult human anterior cruciate ligament (ACL) has poor functional healing response. Transforming growth factor (TGF)-β1 enhances the wound repair by stimulating matrix proteins deposition as well as the proliferation and migration of cells. However, the function of the TGF-β1-induced matrix metalloproteinases' (MMPs) activities in the wound healing process is poorly understood. In this study, exogenous MMP-2 is added to mimic the TGF-β1-induced MMP-2 expression. Role of NF-κB pathway is further examined. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…TGF-b1 and TGF-b2 are expressed during the early inflammatory phase of adult tendon healing; stimulating cell migration, proliferation, and collagen synthesis. [54][55][56][57][58] This situation results in scar tissue formation that strengthens the tendon-bone interface, but does not recreate the architecture and mechanical properties of the native tendon enthesis. 59 Recent studies have identified the role of the TGF-b3 isoform in promoting direct tendon healing without scar formation (scarless healing) in the fetal and neonatal environment.…”
Section: Growth Factor/cytokine-based Augmentation Of Tendon-bone Heamentioning
confidence: 98%
See 1 more Smart Citation
“…TGF-b1 and TGF-b2 are expressed during the early inflammatory phase of adult tendon healing; stimulating cell migration, proliferation, and collagen synthesis. [54][55][56][57][58] This situation results in scar tissue formation that strengthens the tendon-bone interface, but does not recreate the architecture and mechanical properties of the native tendon enthesis. 59 Recent studies have identified the role of the TGF-b3 isoform in promoting direct tendon healing without scar formation (scarless healing) in the fetal and neonatal environment.…”
Section: Growth Factor/cytokine-based Augmentation Of Tendon-bone Heamentioning
confidence: 98%
“…MMP production and activation are increased in the presence of inflammatory signals such as interleukin 1b (IL-1b) and TGF-b1, serving as a key component of the early inflammatory and repair phases of healing. 58,74,75 Local and systemic inhibition of MMP activity in a rotator cuff repair model has shown reduced collagen degradation, increased fibrocartilage production, improved collagen fiber organization, and increased mechanical load to failure. 76,77 Regulating the degradative balance of MMPs may play a significant role in improving the quality and rate of healing at the tendon-bone interface during ACL graft incorporation.…”
Section: Growth Factor/cytokine-based Augmentation Of Tendon-bone Heamentioning
confidence: 98%
“…Increased TGF-β1 facilitates ACL's healing process by promoting fibroblasts migration and proliferation. Fibroblast migration is mediated by MMP-2, and NF-κB pathway is involved in TGF-β1-mediated MMP-2 release that leads to an augmented fibroblast migration and proliferation [38].…”
Section: Biomaterials Scaffoldsmentioning
confidence: 99%
“…Increased TGF-β1 facilitates the ACL healing process by promoting the fibroblasts migration and proliferation [38]. The BMP molecules are osteoinductive cytokines related to the TGF-β family [37].…”
Section: Biomaterials Scaffoldsmentioning
confidence: 99%
“…Stimulation with TGFβ1 alone evoked strong proliferative response of cells from explants of the ACL (8). TGFβ1 induced also dramatic elevation of metalloproteinase 2 (MMP2) activities and the MMP2/tissue metalloproteinase inhibitors (TIMPs) ratio in cells from ACL (9) and significantly increased mRNA level of lysyl oxidase family members (10) while tumor necrosis factor (TNF) downregulated it (11).…”
Section: Introductionmentioning
confidence: 99%